Love in Robert Browning's Poems - Yang, Chunhong (Advances in Social Sciences Research Journal, 2019)
Robert Browning is considered as an optimist, but in his love poems run a torrent of devastation and destruction. Both in his poetry of courtship and poetry of marriage, there are damaging and harrowing love experiences. “Porphyria’s Lover” and “My Last Duchess” are typical examples. Both dramatic personae, motivated by their extreme desire of dominance, murder their beloved ones. Therefore, in Browning’s world of love, the relationships are blighted by loss and disillusion.